The literary heritage of T. Morrison in the context of Afro-American literature of the second half of the ХХ century - Кравець, Олена Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article focuses on researching the literary heritage of T. Morrison in the context of Afro-American writers’ creativity. In the novel “Jazz” by T. Morrison the emphasis is on issues of preserving Afro-Americans’ national identity, deforming modern people’s spirituality under urbanized reality circumstances and on social problems of Afro-American women. It has been revealed that T. Morrison uses the method of interweaving various motives: the motive of jazz, which is the conceptual one in the novel considered, the motives of death, freedom, looking for one’s own identity, and of hicks’ conquering big cities.